Analysis of Marketing Aspects in Tiktok Shop Online Business in Business Feasibility Study Perspective - Alia Fitriyani (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2024)
This study aims to evaluate the effect of customer reviews, live video streaming, free shipping, and discounts on product purchasing decisions in Tiktok Shop, especially among teenagers in Palalang Village, Pakong District, Pamekasan Regency. The research method used is a qualitative approach with data collection through observation, interviews, and documentation. The results showed that positive reviews increased purchasing interest, while negative reviews reduce purchase interest. Live video streaming, free shipping, and discounts are proven to be a significant factor in increasing purchasing decisions. Customer satisfaction plays an important role in influencing purchasing decisions and customer loyalty. This study concluded that an effective marketing strategy at Tiktok Shop can increase customer satisfaction and purchasing decisions, which in turn supports the success of online business.